(untitled) (KIUT Publication, 2025)
This article examines modern approaches to urban-planning and environmental regulation of the placement of solid waste processing (SWP) facilities. An analysis of international practices is presented, with a focus on the integration of these facilities into the urban environment, environmental safety, and architectural adaptation. Attention is paid to the current situation of SWP placement in Uzbekistan, identifying key problems and outlining possible solutions.